2023
DOI: 10.2217/fon-2022-1213
|View full text |Cite
|
Sign up to set email alerts
|

Plain language summary and patient perspective of the European Society for Medical Oncology expert consensus statements on treating EGFR-positive non-small-cell lung cancer

Abstract: What is this summary about? This article provides a plain language summary and patient perspective of a new set of recommendations made by the European Society for Medical Oncology (ESMO for short). These recommendations are also called expert consensus statements. They cover the management of people with a type of lung cancer called epidermal growth factor receptor-positive non-small-cell lung cancer (EGFR-positive NSCLC for short). Why were the recommendations developed? The ESMO Clinical Practice Guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is a biomarker for cancer diagnosis and a therapeutic target in cancer therapy. 29–32 The functions of EGFR in cancer cells have been well studied, but the roles of exosome-derived EGFR are less understood, especially in esophageal cancer. Here, our results indicated that higher EGFR expression was found in exosomes from cell lines with high EGFR expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is a biomarker for cancer diagnosis and a therapeutic target in cancer therapy. 29–32 The functions of EGFR in cancer cells have been well studied, but the roles of exosome-derived EGFR are less understood, especially in esophageal cancer. Here, our results indicated that higher EGFR expression was found in exosomes from cell lines with high EGFR expression.…”
Section: Discussionmentioning
confidence: 99%